Jak inteligentne jest prawo regulujące sztuczną inteligencję? : próba analizy AI Act na podstawie jej ugruntowania w przestrzeni komercyjnego użycia - Palacz, Kamil (Wydawnictwo C.H. Beck, 2023)
The purpose of this study is to present regulations in regard to artificial intelligence, examples of its use and risks it entails. In the present article the author also brings up the subject of the AI Act, analyses the issue of artificial intelligence in the context of civil law and common law, and attempts to answer the question whether AI legislation on our current level of knowledge is accurate legislation.
Keywords: sztuczna inteligencja; AI Act; kategorie AI Act; regulacje prawne sztucznej inteligencji; zastosowanie sztucznej inteligencji